Determination of Suitable Groundwater Quality for Agriculture by Using GIS Application, Bantul Regency, Yogyakarta Special Province, Indonesia - , CHHUON KONG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In order to evaluate groundwater quality for irrigation purpose within Bantul area situated on Yogyakarta-Sleman Groundwater Basin, 47 existing data points were used complementary with the results of analysis from 30 groundwater samples which were collected from dug and tub wells in various locations of study area. ECw, TDS, pH and cations: Na+, Ca2+, Mg2+, K+, and anions: Cl-, HCO3 -, SO4 2-, NO3 - were analyzed. The relative tendency of ion in epm shows Ca2+>K+>Na+>Mg2+ and HCO3 ->Cl->SO4 2-. Variations in groundwater composition using Mg/Ca vs. Na/Ca in molar ratio, indicates groundwater is close to silicate rock with influence of clastic carbonate rock. Higher salinity approach to the west of the Bantul, indicates that groundwater quality is controlled by clastic carbonate rock of Sentolo Hills. Groundwater samples fall under class I suggested that groundwater is good and suitable for irrigation based on Doneenâs classification of Permeability Index and 78.37% is in excellent category by Wilcox classification on Sodium Percentage (Na%). According to the Sodium Adsorption Ratio (SAR) values plotted in the USSL diagram, the majority of the groundwater samples belong to C2-S1 and C2-S2 class, indicating medium salinity and low sodium water which can be used for irrigation with little danger. Salinity is the significant problem has slight to moderate restriction on crops productivities in this area. The ECw map indicates good groundwater quality for crops is at the middle to the east of study area close to Opak River, while at the western effects irrigation water but no reduction on rice productivity. The suitability of groundwater quality for agriculture is determined by thematic maps produced from ArcGIS Spatial Analyst based on FAO guideline. The slight to moderate restriction on sensitive crops indicating with different yield potential in the agricultural land in which 100%, 90% and 75% of yield potential correspond to about 2727.90 ha, 735.49 ha and 208.98 ha of the study area respectively.